A new approach to solving split equality problems in Hilbert spaces. (9th December 2022) - Reich, Simeon; Tuyen, Truong Minh
Abstract : Using a product space approach, we propose and study several iterative methods for solving certain types of split equality problems in Hilbert spaces.